Problematika Kinerja Pendidik di Lingkungan Pendidikan Islam - Gani, Muhammad Abdul (Asosiasi Mahasiswa Program Pascasarjana | Institut Agama Islam Darussalam | IAID | Ciamis | Jawa Barat, 2020)
This article highlights the problems faced by educators in the Islamic education environment. Islamic identity in Islamic educational institutions is not a reason for educators to live and carry out their duties properly and professionally. The lack of awareness of this causes educators to pay less attention to the quality of the educational process provided. The difference in ministerial nomenclature that houses educational institutions also indirectly influences many matters relating to the activities of teachers as professional educators. In addition, other issues that have become the problem of educators in the Islamic education environment occur due to internal and external factors of educators, including official operational problems and institutions, educators' competencies and qualifications, welfare and leadership crisis in Islamic education institutions. This research uses literature review method by searching various sources of literature that are relevant to the research subject.